Islamic State's online propaganda : a comparative analysis - Lakomy, Miron (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Explaining the means utilized by the editors of the Islamic State's online magazines to win the "hearts and minds" of their audiences, this book is a result of a multidimensional content analysis of two flagship periodicals of the IS - Dabiq and Rumiyah. Drawing from a number of theoretical concepts in propaganda studies, the research uses comparative analysis to understand the evolution of the modus operandi employed by the editorial staff. The volume evaluates the types of arguments used in these magazines, as well as the emotions and behaviour that these triggered in readers. This book concentrates on the formats and thematic composition of a variety of the Islamic State's e-periodicals, including Dabiq, Rumiyah, Dar al-Islam or Konstantiniyye, from the viewpoint of the constantly changing strategic situation and priorities of the "Caliphate." The e-magazines of the post-territorial phase of the Islamic State, e.g. From Dabiq to Rome and Youth of the Caliphate, were also taken into consideration. Overall, this book does not only offer new insights into the propaganda methods of the Islamic State's periodicals, but it also summarizes their rise and fall between 2014 and 2019. The volume is dedicated mostly to academics and postgraduate students specialized in terrorism studies, political violence and security studies"--
Going virtual : Islamic State's shock and awe campaign on the Internet -- United they stand : rediscovering the thematic landscape of the "Caliphate's" eperiodicals -- Reading between the lines : understanding the propaganda techniques exploited by Dabiq and Rumiyah.
OCLC-licensed vendor bibliographic record.
Keywords: IS (Organization); Propaganda; Internet and terrorism; Electronic journals -- Political aspects; POLITICAL SCIENCE / Political Freedom & Security / Terrorism; SOCIAL SCIENCE / Media Studies